A finite deformation constitutive model for brain white matter considering the time-dependent and damage behaviors of matrix and axonal fibers - Xia, Bing; Fan, Lei; He, Ge (Mechanics of materials, 2025)
This work aims to develop a novel two-phase constitutive model to capture the hyperelastic, time-dependent, and damage behaviors of extracellular matrix and axonal fibers of brain white matter. Within the continuum damage mechanics framework, the Ogden model was used to describe the hyperelastic and viscous behavior of the matrix, while exponential and second-order power functions were employed to represent the similar behavior of fibers. The damage evolutions in both the matrix and fiber phases of the brain white matter were represented using sigmoid functions. The developed two-phase viscohyperelastic-damage constitutive model was calibrated and validated using the experimental data of the corpus callosum of brains. Specifically, the model was calibrated and validated using experimental data collected under various loading conditions, including uniaxial tension, uniaxial compression, simple shear, stress relaxation, and cyclic loading. The comparison of predicted results and experimental data demonstrated that this constitutive model effectively captures the mechanical behaviors of brain white matter, such as nonlinear elasticity (hyperelasticity), stress softening (damage), and time-dependent effects (strain rate dependence, stress relaxation, and cyclic loading responses), and it has capabilities of separately modeling the fiber and matrix phases of the brain tissue. •A brain tissue constitutive model separately considering the behaviors of fiber and matrix phases.•The model can capture the hyperelastic, time-dependent and damage behaviors of each phase.•The model holds promise for enhancing comprehension of brain tissue damage and injury.•The model can be integrated into FEA software to support optimization of head protection equipment such as helmets.